Mixed grazing systems of goats with cattle in tropical conditions: an alternative to improving animal production in the pasture. (18th July 2014) - d'Alexis, S.; Periacarpin, F.; Jackson, F.; Boval, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Mixed grazing systems combining sheep and cattle have shown better growth performance for one or both species. This observation has been attributed to their complementary feeding behaviour and the reduced host infection by gastrointestinal nematodes. Less attention has been paid to mixed grazing systems combining goats and cattle. Here, continuously grazing goats mixed with cattle (M) were compared with control goats reared alone (C) under tropical conditions. The comparison was conducted with gastrointestinal nematode-infected (I) and non-infected (nI) goats. Thus, the four treatments were cattle with gastrointestinal nematode-infected goats (MI), gastrointestinal nematode-infected goats alone (CI), cattle with non-infected goats (MnI) and non-infected goats (CnI). Average daily gain (ADG, g/day) and grass production were measured for the four groups of animals (six goats and two heifers treated with MI or MnI) grazing for 3 months on 4 subplots. Monthly measurements were performed over 5-day periods. This pattern was replicated in space for a second set of four subplots and in time for six successive cohorts of animals (bands 1 to 6). The ADG of goats in mixed grazing conditions was higher than controls irrespective of the infection status (32.6 v. 18.4 g/day for MI v. CI; 44.2 v. 33.5 g/day for MnI v. CnI). Concomitantly, the average biomass was lower for mixed grazing animals compared with controls (174 v. 170 for MI and MnI; 235 v. 208 for CI and CnI, respectively), suggesting better use of the sward. For daily BW gain (g/kg DM), mixed grazing also yielded better results than the control (1.88 v. 0.52 g BW/kg DM per day for MI v. CI; 2.08 v. 1.47 g BW/kg DM per day for MnI and CnI). Mixed grazing of goats and heifers offers a promising alternative for increasing goat and overall animal production as well as improving the management of pastures.